Knowledge management for process, organizational and marketing innovation : tools and methods - O'Brien, Emma.; Clifford, Seamus; Southern, Mark, 1967- (Hershey, PA : Information Science Reference, 2011)
'This book outlines different tools and technologies that can be applied depending on the type of innovation an organization desires, providing concrete advice on the different types of innovation, situations in which innovation may be useful and the role of knowledge and different tools and technologies to support it'--Provided by publisher.
Includes bibliographical references and index.
Keywords: Knowledge management; Diffusion of innovations; New products